Thermal and structural modification in transparent and magnetic germanoborate glasses induced by Gd2O3 - Fernandes, Roger Gomes [UNESP]; Franco, Douglas Faza [UNESP]; Mastelaro, Valmor Roberto; Cardinal, Thierry; Toulemonde, Olivier; Nalin, Marcelo [UNESP] (Elsevier, 2020)
A series of new transparent and magnetic germanoborate glasses in the system (100-x)[60GeO2–25B2O3–10Na2O–4Al2O3–1PbO] – (x) Gd2O3, with x = 0, 1, 2, 5, 10, 15 and 20 mol%, was prepared and studied with respect to their thermal and structural changes in the presence of Gd2O3. Based on Differential Scanning Calorimetre (DSC) analysis, a glass with 5% of Gd2O3 showed a high thermal stability, which progressively decreases for samples with higher content of Gd2O3. By the analysis of Raman and Fourier Transform Infrared (FTIR) spectra, it was possible to identify that by increasing the amount of Gd2O3, a progressive depolymerization of 6-membered Ge[IV] rings is promoted, concomitant with an increase of Ge[IV] tetrahedra units with non-briding oxygens. The structural analysis through the local-sensitive techniques EXAFS (Extended X-ray Absorption Fine Structure) and XANES (X-ray Absorption Near Edge Structure) showed that the short-range structural modification around the elements Ge and Gd3+ does not change with the addition of Gd2O3 and the presence of germanium four-fold coordination [GeIV] and Gd3+ states, respectively. A simulation of the coordination number (N), the interatomic distance (R) of Ge–O and Gd–O bonds and the Debye-Waller factor was also carried out. The microstructure, after crystallization, of the sample with 15 mol% of Gd2O3 was evaluated using optical and electron microscopes. Finally, the paramagnetic behaviour and ion probe quantification of Gd3+ ions were obtained based on magnetic susceptibility measurements.
Keywords: Germanoborate glasses; Magnetic susceptibility; Magneto-optical materials; Vibrational spectroscopy; X-ray absorption spectroscopy